William Friday : Power, Purpose, and American Higher Education. - Link, William A. (The University of North Carolina Press, 1997)
Few North Carolinians are as well known or as widely respected as William Friday. Although he has never run for elected office, the former president of the University of North Carolina has been prominent in public affairs for decades and ranks as one of the most important American university presidents of the post-World War II era. In this comprehensive biography, William Link traces Friday's long and remarkable career. Friday's thirty years as president of the university, from 1956 to 1986, spanned the greatest period of growth for higher education in American history, and he played a cr.